"My Walking is My Dancing": The Relationship between Dance and Music in Anne Teresa De Keersmaeker's Work. Issue 3 (14th September 2022) - Rutgeerts, Jonas
Abstract: Throughout her career the Belgian choreographer Anne Teresa De Keersmaeker has created different techniques to engage in an intimate relationship with musical compositions, using these compositions to drive the development of her choreographic oeuvre. I argue that walking can be defined as one of the main choreographic devices used in De Keersmaeker's late works. In analyzing En Atendant (2010) and Cesena (2011), I explore how De Keersmaeker uses walking to inscribe the bodies of the dancers into the music.